The Relationship Between Halal SMEs Social Capital and Foreign Market Knowledge (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the influence of social capital dimension in network relationships on foreign market knowledge. Three key dimensions of social capital in network relationships were measured in this study are structural dimension, relational dimension and cognitive dimension. This study used quantitative data collection method, a total of 107 managers/decision makers have participated in the survey. The results were analysed using SEM- Partial Least Squared (PLS) technique. The researcher found that structural dimension and relational dimension have significant effect with foreign market knowledge. This suggest that Halal SMEs in Malaysia were focusing on structural and relational dimension in building their foreign market knowledge.